Assessment of Environmental Risks from Pollution by Toxic Emissions in Heat Treatment Process of Electrode Production - IVANENKO Olena; VAHIN Andrii; SHABLIY Tetyana; TERESHCHENKO Oksana; SHVACHKO Denis; PLASHYKHIN Sergii; PAVLIUK Nonna (Architecture, Civil Engineering, Environment)
The purpose of this work is to assess the risks to the health of the population living in the zone of influence of emissions of pollutants into the atmospheric air from the operating enterprise for the production of carbon electrodes and to generalize the experience of applying the procedure for assessing risks and damage to the health of the population in the system of new monitoring and management mechanisms air quality. The risk assessment of the impact of planned activities on the health of the population from atmospheric air pollution was carried out based on the risk calculations of the devel-opment of non-carcinogenic and carcinogenic effects. During the assessment of the risk to public health from the emissions of the enterprise for the production of carbon electrodes, carbon monoxide was identified as one of the priority pollutants, to reduce the emissions of which it is proposed to use catalytic methods in the furnaces for firing and graphitizing carbon electrodes. Based on the results of the conducted research, it is proposed to introduce technologies that will allow to achieve the maximum permissible emissions of pollutants into the atmosphere during heat treatment.